Peningkatan Keterampilan Menulis Cerpen Melalui Model Pembelajaran Kooperatif Type Jigsaw Berbantuan Media Audiovisual Pada Siswa Kelas XI MIPA 2 SMA Darum Ulum Poncol Magetan Tahun Pelajaran 2020 - -, Puriyani; Teguh Suharto; Dwi Rohman Soleh (Pusat Studi Pendidikan Kreatifitas Anak Wadas Kelir Purwokerto, 2021)
This study aims to: (1) describe the learning process of writing short stories with the Cooperative Learning Model Type Jigsaw Assisted by Audiovisual Media in Class XI MIPA2 Students of SMA Darul Ulum Poncol and (2) describe the short story writing skills with the Cooperative Learning Model Type Jigsaw Assisted by Audiovisual Media for Students Class XI MIPA2 SMA Darul Ulum Poncol. This research is a Classroom Action Research (PTK) with the research subject of writing skills of class XI MIPA2 SMA Darul Ulum Poncol, Magetan in two cycles. Each cycle contains four components, namely planning, implementing, observing, and reflecting. The results showed: (1) the learning process of writing short stories with a cooperative approach to the type of audiovisual assisted jigsaw has increased. Before the study, the average score for class 68 was below the minimum completeness criteria, namely 75. In the first cycle, the average score was 74. 63% or 24 students have reached the minimum completeness criteria (KKM). However, this percentage has not met the achievement indicators, namely 75% or 29 students scored above the KKM. In Cycle II, the students' average short story writing score increased to 78. Of the 38 students, 31 students or 82% had achieved the minimum completeness score.